The Benign Side of the Abdominal Wall: A Pictorial Review of Non-Neoplastic Diseases - Giorgia Porrello; Federica Vernuccio; Eduardo Alvarez-Hornia Pérez; Giuseppe Brancatelli; Roberto Cannella (Diagnostics, 2022)
The abdominal wall is the location of a wide spectrum of pathological conditions, from benign to malignant ones. Imaging is often recommended for the evaluation of known palpable abdominal masses. However, abdominal wall pathologies are often incidentally discovered and represent a clinical and diagnostic challenge. Knowledge of the possible etiologies and complications, combined with clinical history and laboratory findings, is crucial for the correct management of these conditions. Specific imaging clues can help the radiologist narrow the differential diagnosis and distinguish between malignant and benign processes. In this pictorial review, we will focus on the non-neoplastic benign masses and processes that can be encountered on the abdominal wall on cross-sectional imaging, with a particular focus on their management. Distinctive sonographic imaging clues, compared with computed tomography (CT) and magnetic resonance (MR) findings will be highlighted, together with clinical and practical tips for reaching the diagnosis and guiding patient management, to provide a complete diagnostic guide for the radiologist.